Location of first attack predicts the site of subsequent relapses in multiple sclerosis. (April 2020) - Tsantes, Elena; Leone, Maurizio A.; Curti, Erica; Cantello, Roberto; Vecchio, Domizia; Granella, Franco
Highlights: The location of first attack influences the site of subsequent ones in RRMS. Side of relapses and time elapsed between attacks don't impact the attacks location. Patients on DMT relapsed more frequently in the SC, compared to untreated ones. Abstract: Predictors of attack location in relapsing-remitting multiple sclerosis (RRMS) are poorly known. It has been suggested that the site of the first relapse may influence the location of the subsequents. We aimed to ascertain this hypothesis in a sample of patients consecutively recruited in two Italian MS Centres, with at least two MS attacks. The following data were collected from medical records: demographic data, locations involved in the first two (or three) MS attacks (optic nerve, spinal cord, brain stem/cerebellum, cerebral hemispheres, according to symptoms presented), time elapsed between relapses and onset of disease-modifying treatment (DMT). We enrolled 199 patients (67% females; MS onset age 30.0 ± 8.69 years), in 148 of whom we could define the precise attack location. In 70/148 patients (47%) the second attack involved exactly the same location as the first. There was an increased risk of relapsing in the same location of the first attack when this involved the optic nerve (OR 4.5, 95% CI 2.2–9.2, p < 0.0001), the brainstem/cerebellum (OR 3.5, 95% CI 1.7–6.9, p < 0.0001), or the spinal cord (OR 3.0, 95% CI 1.5–5.9, p = 0.001). The location of third relapse (N = 90) was equally influenced by the site of first attack. In 24 patients with optic neuritis in both the two first attacks, the side coincided in 50% of cases. The location of first attack has a major role in influencing the site of subsequent ones in RRMS.